Prevalence of food addiction determined by the Yale Food Addiction Scale and associated factors: A systematic review with meta‐analysis. (24th December 2021) - Praxedes, Dafiny R. S.; Silva‐Júnior, André E.; Macena, Mateus L.; Oliveira, Ana Débora; Cardoso, Kamyla S.; Nunes, Lara O.; Monteiro, Maíra B.; Melo, Ingrid Sofia V.; Gearhardt, Ashley N.; Bueno, Nassib Bezerra
Abstract: Objective: To determine, through a systematic review with meta‐analysis, the prevalence of food addiction (FA) using the Yale Food Addiction Scale (YFAS) and its derivatives exploring possible factors associated with the prevalence of FA in several contexts. Methods: The following databases were searched: MEDLINE, ScienceDirect, LILACS, PsycArticles, CENTRAL, Greylit.org, and OpenGrey.eu . Studies that assessed FA using YFAS were included. Two independent reviewers assessed the eligibility of each report. Random‐effects meta‐analysis was performed to calculate the weighted prevalence of FA. Subgroup analyses and meta‐regression were conducted to explore sources of heterogeneity. Results: Of the 6425 abstracts reviewed, 272 studies were included. The weighted mean prevalence of FA diagnosis was 20% (95% CI: 18%; 21%). The prevalence of FA was higher in individuals with clinical diagnosis of binge eating (55%; 95% CI 34%; 75%). The prevalence in clinical samples was higher compared to non‐clinical samples. Two studies included children only and no studies included only elderly people. Conclusions: Food addiction is a topic in which there has been a significant growth in studies. The highest prevalence was found in the group of participants with eating disorders and weight disorders. More studies with children and the elderly are needed. Highlights: There was an exponential increase in the number of scientific publications related to food addiction. The overall prevalence of food addiction was 20%. The highest prevalence of food addiction was found in the group with a clinical diagnosis of binge eating. Studies conducted in clinical settings in general also showed high prevalence of food addiction.